Anionic surfactants enhance click reaction-mediated protein conjugation with ubiquitin. Issue 5 (1st March 2016) - Schneider, Daniel; Schneider, Tatjana; Aschenbrenner, Joos; Mortensen, Franziska; Scheffner, Martin; Marx, Andreas
Graphical abstract: Abstract: The Cu(I)-catalyzed alkyne–azide cycloaddition (CuAAC) has become increasingly important in the conjugation chemistry of biomolecules. For example, it is an efficient and convenient method to generate defined ubiquitin–protein conjugates. Here, we investigate the effect of surfactants on the efficiency of CuAAC for chemical protein ubiquitylation. We found that anionic surfactants enhance conjugate formation by up to 10-fold resulting in high yields even at low (i.e., micromolar) concentrations of the reactants. Notably, the herein investigated conjugates are functional and thus properly folded.